Site and hybrid-specific agrotechnical models in sweet corn production - Lente, Ádám (Acta Agraria Debreceniensis, 2011)
The effect of three agrotechnical factors (sowing time, fertilization, plant density) and two genotypes on the crop yield of sweet corn was examined on chernozem soil in the Hajdúság region in two different crop years. Compared to the 30-year average, the climate was dry and warm in 2009 and humid in 2010. The experiments were conducted at the Látókép Research Site of the University of Debrecen. In the experiments we applied two sowing times (end of April, end of May), six fertilization levels (control, N30+PK, N60+PK, N90+PK, N120+PK, N150+PK) and two crop density levels (45 thousand ha-1, 65 thousand ha-1). The hybrids we used were Jumbo and Enterprise. As regards the requirements of sweet corn production, the crop year of 2009 was dry and warm. The effect of moisture deficiency was more adverse on the crop yields with the second sowing time. On the contrary, the other examined year (2010) was significantly humid; the precipitation was 184 mm above the 30-year average and the temperature was average.In the dry and hot crop year, the best yields were obtained with the hybrid Jumbo (25677 kg-1) at 65 thousand ha-1 plant density level on the average of the fertilization levels. The crop yields of Enterprise were also the highest at high plant density level (24444 kg ha-1). With the second sowing time the highest yields were obtained at the higher plant density level (65 thousand ha-1) with both hybrids (Jumbo 18978 kg ha-1, Enterprise 18991 kg ha-1), which confirmed the good adaptation capability of these hybrids at high plant density level. In humid crop year with early sowing time the highest yielding hybrid was Enterprise (at 45 thousand ha-1 crop density level 20757 kg-1), at the same time, Jumbo was best yielding at the higher plant density level (18781 kg-1). With the second sowing time the highest crop yield was obtained with Enterprise again (20628 kg ha-1 at 65 thousand ha-1 plant density level). With this sowing time the average yields of Jumbo, was 18914 kg ha-1 respectively. We found that dry crop year and early sowing time provided the best conditions for sweet corn production; the highest yields were obtained under these circumstances, which might be the results of the outstanding water management of chernozem  soils.